Human groups arriving in Algiers during the Islamic middle age - Quraishan, Abdul Qadir (The Algerian Historical Journal, 2026)
Algiers is one of the most important coastal cities of the Islamic middle age, with its natural and human elements that have enabled it to establish a prominent position among the cities of the Islamic Maghreb in general and the Middle East in particular. Perhaps the most important characteristic of this city during this period is the phenomenon of delegations of human groups (Arabs, Andalusians, Jews and Christians) on the city during Islamic middle age, so that these groups, along with the local elements (Bani Mazghani tribe) contributed to the development of the city politically, economically and culturally, as its system of government shifted from tribal to emirate system, as well as from an agricultural city at the beginning of the 3rd century AH (9th AD), to a commercial city thanks to the contribution of these groups to the revitalization of the economic movement of the city and To a scientific metropolis among the most important Moroccan cities by the end of the 9th century AH(15th century AD). Through this article, I wanted to reveal the most important human groups that came to Algiers during the Islamic middle age, and the reasons behind these delegations, as well as to highlight their political, economic and cultural influences on the city during the the Islamic middle age.